PENGARUH NILAI FUNGSIONALDAN NILAI EMOSIONAL TERHADAP NIAT BELI YANG DIMEDIASI OLEH SIKAP PEMBELIAN PADA KONSUMEN PRODUK AIR MINUM DALAM KEMASAN DI KOTA BANDA ACEH - Nailul Muna; Jasman J. Ma’ruf (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
The aim of the study is to measure the effect of Functional Value and Emotional Value on Purchase Intention Mediated by Purchasing Attitudes on Consumers of Packaged Drinking Water Products in Banda Aceh City. The samples of this study consist of 200 respondents who consistently consume the packaged drinking water. Data collection tools used in this study was questioners and Google form. The sampling technique used was accidental sampling. AMOS Structural Equation Modeling (SEM) was used as the analysis method to determine the effect of the variables involved. Based on the results of the analysis that has been conducted, it indicates that Functional Value and Emotional Value have an effect on Purchasing Attitudes, Purchasing Attitudes have a positive effect on Purchase Intention and Purchasing Attitudes partially mediate the relationship between Functional Value and Emotional Value on Purchase Intention.